Pengembangan bahan ajar Mata Kuliah Kajian Seni Rupa Lokal pada Program Pascasarjana Universitas Negeri Makassar - Pangeran Paita Yunus; Abd Aziz Ahmad (Seminar Nasional LP2M UNM, 2019)
This study aims to 1) Develop local art teaching materials with the aim of knowing the ability to understand, appreciate, and analyze students in aspects of historical background, concepts, and artwork in South Sulawesi 2) Measuring the feasibility of local art teaching materials in the Postgraduate Program in Arts Education Study Program Universitas Negeri Makassar. This research refers to the development procedure developed by Borg & Gall which consists of ten steps that are arranged systematically, with easy-to-understand explanations, and can direct the developer from the beginning to the end of the study. In research on the development of teaching materials, it was only carried out up to nine steps, product dissemination or distribution activities were not carried out due to limited funds and time of the researcher. The components of the learning package developed in this study are textbooks, media presentations, and appreciation tests. The stages in research and development of this instructional package consist of four phases: the initial study phase and the development phase, the implementation phase, the testing and evaluation phase. Learning packages for Local Art Studies in the form of teaching materials, media presentations and appreciation test sheets produced in this study are feasible packages to be used in the learning process in the subject of Local Art Studies at the Universitas Negeri Makassar Postgraduate Program in Fine Arts Education. This is because the package developed has fulfilled the validity criteria, practicality, and effectiveness.